Matrix Transforms of Summability Domains of Normal Series-to-Series Matrices - Ants Aasma (Journal of Advances in Applied & Computational Mathematics, 2015)
In the present paper matrix transforms of summability domains CSA of normal series-to-series matrices A are investigated. Let M be a matrix and B a triangular series-to-series matrix. Necessary and sufficient conditions for M to be a transform from CSA into CSB are found. For application the special case, when A is a series-to-series Riesz matrix, are studied.